L'étude de controverses pour une connaissance des pratiques et des institutions de recherches technoscientifiques - Virginie Albe (Université de Provence, 2022)
Socio-technical controversies can be an object of learning about democracy and a way to foster empowerment of students, through confrontation with a diversity of points of view. It is a question of developing among young people, from the identification of the actors of the controversy and a work on their interests and their arguments, an epistemological complexification and to train them socio-politically, by keeping away the binary approach (for/against) which often structures the media presentations of controversies, and their pedagogical treatment. The analysis of the framing effects of the pedagogical sequence co-constructed with professionals (teachers and researchers) shows here that the pupils reproduce the discourse of the public debate by positioning themselves in favor of nanotechnologies as a responsible innovation, but in the same time pupils ethically reject the transhumanist perspectives of manipulation of the living and the human being. They also question the interest of nanotechnologies in spaces of deliberation without a pedagogical framework. Such results invite us to (re)consider the formats for dealing with controversies in science classes.